The persuasive aims of Metal Gear Solid: A discourse theoretical approach to the study of argumentation in video games. (March 2017) - Stamenković, Dušan; Jaćević, Milan; Wildfeuer, Janina
Abstract: The paper is aimed at proving the hypothesis that multimodal construction in video games can follow specific discursive aims in the process of persuading game players. In order to prove this, we have performed a multifaceted analysis which elaborated the ways in which different modalities in a representative video game combine so as to convince the player to act, play, and perhaps think accordingly. The multimodal approach employed in the paper combines the notion of discourse aims and the rhetorical and argumentative structure of Metal Gear Solid (Kojima, 1998 ), and analyses different narrative strategies and verbal cues, as well as the overall interface, control, and gameplay. The results suggest that verbal and textual cues combine with audio-visual elements and highly specific gameplay strategies in order to refrain the player from killing enemies. This might indicate that video games are likely to possess a great persuasive power, as they are both multimodal and highly interactive. Highlights: Multimodal construction in video games can follow discursive aims and persuade. The paper elaborates the ways in which different modalities in a video game combine. We analyse different narrative strategies, the interface and gameplay. Verbal cues combine with audio-visual elements to refrain the player from warfare. Video games are likely to possess a great persuasive power.